Dynamic Chiral Metasurfaces for Broadband Phase‐Gradient Holographic Displays. Issue 5 (11th January 2023) - Naeem, Taimoor; Kim, Joohoon; Khaliq, Hafiz Saad; Seong, Junhwa; Chani, Muhammad Tariq Saeed; Tauqeer, Tauseef; Mehmood, Muhammad Qasim; Massoud, Yehia; Rho, Junsuk
Abstract: Next‐generation holographic displays have promising applications in medical science, augmented/virtual reality, smart security, data encryption, etc. Although metasurfaces emerged as the suitable choice to provide compact holographic displays, multifunctionality in metasurfaces at broadband optical wavelengths is inevitable for the abovementioned applications. Here, a metasurface is demonstrated based on chiral structures to introduce multifunctionality in terms of multiple wavefront information depending upon the polarization of incident light. The proposed metasurface integrated with a liquid crystal (LC) provides fast switching and dynamic optical response at broadband visible wavelengths in transmission mode. To avoid the phase distortion in multiple wavefront information embedded into a single planar metasurface, chiral z‐shaped meta‐atoms are used to provide high diffraction efficiency and phase chirality response for circularly polarized (CP) light illuminations. The phase mask of holographic information is encoded into the metasurface using a combination of dynamic and geometric phase modulation techniques. The experimental validation of the designed metasurface is performed to reproduce the spin‐dependent‐specific information at broadband visible wavelengths for changing the polarization of incident light. This research may pave the way toward designing highly efficient multifunctional metadevices to produce next‐generation holographic displays for promising applications in healthcare, media, smart security, and data encryption. Abstract : Next‐generation holographic displays have promising applications in medical science, augmented/virtual reality, smart security, data encryption, etc. This work demonstrates a chiral metasurface integrated with a liquid crystal (LC) cell that provides dynamic phase‐gradient holographic displays at braodband visible wavelengths. This research may pave the way toward designing highly efficient multifunctional metadevices to produce next‐generation holographic displays.